Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Pt Alfamart Jl. Bambu, Medan - Zega, Ellen Gracia; Siagian, Nalom; Sinaga, Kepler (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
In the current era of globalization, the business world has experienced significant developments, especially the retail business. PT Alfamart is one of the retail businesses with the highest consumer value in Indonesia that provides daily needs. This study aims to determine whether Service Quality and Price affect Customer Satisfaction at PT Alfamart Jl. Bambu, Medan. Research Method: Shows that Service Quality (X1) does not have a positive and significant effect on Customer Satisfaction (Y), Price (X2) has a positive and significant effect on Customer Satisfaction (Y). While Service Quality (X1) and Price (X2) simultaneously have a significant effect on Customer Satisfaction (Y). Conclusion: The results of this study can be concluded that Service Quality (X1) does not have a positive and significant effect on Customer Satisfaction (Y), Price (X2) has a positive and significant effect on Customer Satisfaction (Y), while Service Quality (X1) and Price (X2) simultaneously have a significant effect on Customer Satisfaction (Y).